Ageing, productivity and wages in Austria: Evidence from a matched employer-employee data set at the sector level - Bernhard Mahlberg; Inga Freund; Alexia Prskawetz (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2011)
In this paper we analyse the link between the age structure of the labour force and average labour productivity at the intermediate level of economic sectors. The analysis is based on a panel data set ranging over six years (2002-2007) and covers the sectors of mining, manufacturing and market oriented services in the Austrian economy. Our results exhibit a positive correlation of the share of older employees and productivity, while we cannot find any evidence for a significant relationship of the share of younger employees and productivity. Moreover, the estimated age-wage pattern does not hint at an over-payment of older employees.
Keywords: J14; J24; J82; 330; ageing workforce; production function; age-productivity profile; age-wage pattern